Turning of the tide: Changing systems to address smoking for people with a mental illness - Bonevski, B.; Bowman, J.; Richmond, R.; Bryant, J.; Wye, P.; Stockings, E.; Wilhelm, K.; Butler, Tony; Indig, D.; Wodak, A. (2011)
Smoking tobacco is common among people with a mental illness. A number of behavioural and environmental factors underlie the high smoking prevalence rates. Evidence suggests that smokers with mental illness require additional targeted support to help them stop smoking. By using a selective review of the international literature, this article will argue that a systems-level change approach is an appropriate strategy, targeting settings and environments with a number of advantages for reaching smokers with mental illness. Systems-level changes include: (1) implementing a system of identifying and recording smoking status;(2) providing education, resources and feedback to promote staff intervention;(3) dedicating staff to provide tobacco-dependence treatment;(4) promoting organisational policies that support and provide tobacco-dependence services. Three settings will be discussed - mental health services, community social service organisations and prisons. As a result of a history and culture where smoking was used as part of the system, introducing changes in these settings has to date been challenging. However, with increased awareness of the detrimental health and financial consequences of smoking, the tide appears to be turning to a culture increasingly supportive of smoking cessation. We illustrate this trend using three Australian case studies where smoking is starting to be addressed through changes to systems. © 2011 Taylor & Francis.